Pengembangan Komik Fisika Sebagai Media Pembelajaran Fisika Di Kelas VIII MTSN 1 Lubuk Basung - Aswirna, Prima (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This study aims to produce comic as a medium learning in MTsN 1 Lubuk Basung valid and practical. The research is research and development (R&D). The development of done with reference to a model with 4-D definition, stage, design, develop, dissemination, this research is restricted to development on the stage. The analysis of data obtained the value of the validation comic media 84,36 very valid criteria, the value practical comic media by teachers 93,03 very practical criteria, the value practical comic media by students 82,07 very practical criteria.